Molecular prevalence of giardia duodenalis and subtype distribution (assemblage e and b) in calves in Siirt, Turkey - AKYILDIZ, GÜRKAN (My University, 2023)
Giardia duodenalis is a common intestinal protozoan parasite that infects domestic and wild mammals, birds, and humans, especially livestock, worldwide. Studies on the prevalence of Giardia duodenalis in calves in Turkey are very limited. The aim of this study was to determine the molecular prevalence and subtype distribution of Giardia duodenalis in calves in Siirt. The animal material of the study consisted of 100 calves of different breeds and sexes in Siirt province. Using a disposable latex glove, feces samples were taken from the rectum of each calf and put in separate fecal containers. Sex and age information was recorded for each sample collected. As a result, 5% and 9% positivity was detected by microscopic and nested-PCR methods, respectively. The prevalence was 9.68% in females and 7.89% in males (P>0.05). Prevalence by age groups was as follows: 11.32% in the 1-6 month group, 7.41% in the 7-12 month group, and 5% in the older than 12 months group (P>0.05). As a result of the sequence analysis of the five PCR-positive samples, 80% Assemblage E and 20% Assemblage B were detected. As a result of this study, in addition to Assemblage E, Assemblage B was detected as well, which also has zoonotic properties. This situation may pose a risk for breeders. To better understand the distribution of G. duodenalis assemblages in calves in Siirt, studies in larger herds are needed.
Keywords: Veteriner Bilimleri; Klinik Öncesi Bilimler; Veteriner Parazitoloji; Yaşam Bilimleri; Mikrobiyoloji; Parazitoloji; Sağlık Bilimleri; Temel Bilimler; Veterinary Sciences; Pre-Clinical Sciences; Veterinary Parasitology; Life Sciences; Microbiology; Parasitology; Health Sciences; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Bitki ve Hayvan Bilimleri; Doğa Bilimleri Genel; VETERİNERLİK BİLİMLERİ; ÇOK DİSİPLİNLİ BİLİMLER; MİKROBİYOLOJİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); PLANT & ANIMAL SCIENCE; NATURAL SCIENCES, GENERAL; MICROBIOLOGY; VETERINARY SCIENCES; MULTIDISCIPLINARY SCIENCES; At; Veterinerlik (çeşitli); Genel Veterinerlik; Mikrobiyoloji (tıbbi); İmmünoloji ve Mikrobiyoloji (çeşitli); Multidisipliner; Equine; Veterinary (miscellaneous); General Veterinary; Microbiology (medical); Immunology and Microbiology (miscellaneous); Multidisciplinary